A novel role for multifunctional NAC transcription factor SlNOR-like1: Enhancing flavonoid accumulation in tomato fruit exocarp by modulating glycosylation modification - Gangshuai Liu; Yueming Tang; Yiwen Yang; Jinghong Luo; Xiaodan Zhao; Daqi Fu; Jia Gao (Food Bioscience, 2026)

Decoupling natural ventilation and traffic noise in railway-adjacent dwellings: Field measurements and passive design strategies - Qi Zhao; Chen Chen; Meng Ouyang; Yitong Wang; Yueming Wen (Energy and Buildings, 2026)

Differential effects of Cl- and SO42- anion systems on Ca2+-Mg2+-Mn2+ carbonate biomineralization induced by the halophilic Bacillus dokdonensis: Implications for Mn2+-containing saline wastewater treatment - Xueting Chen; Yueming Zhao; Hui Zhao; Memon Kashif Ali; Ran Shu; Bo Liu; Boyu Cai; Runxi Yin; Zuozhen Han; Huaxiao Yan (Journal of Hazardous Materials, 2026)

Towards low-carbon grain storage buildings: a systematic review of assessment methods and mitigation strategies - Ruoting Liu; Fei Yu; Meng Ouyang; Qi Zhao; Yueming Wen (Energy and Buildings, 2026)

Nitrogen nutrition diagnosis of sweetpotato based on critical nitrogen dilution curve under different water conditions - Xu Zhao; Ximing Xu; Jing Yu; Minghuan Jin; Siyu Wang; Yueming Zhu; Guoquan Lu; Zunfu Lv (Irrigation Science, 2026)

A comparative bioprocess for nutrient reclamation: Suspended versus immobilized Virgibacillus salexigens XYD drives struvite recovery from eutrophic saline water - Na Guo; Yueming Zhao; Shuqi Wang; Yanhong Zhao; Yudong Xu; Memon Kashif Ali; Huaxiao Yan; Hui Zhao; Zuozhen Han; Maurice E. Tucker; Chao Han; Yanyang Zhao; et al. (Journal of Environmental Management, 2026)

Suppressing spectral broadening via intramolecular noncovalent interactions for high-efficiency solution-processed multi-resonance TADF OLEDs - Tao Zhou; Guimin Zhao; Yumiao He; Taiping Chen; Wenwen Tian; Yueming Sun; Wei Jiang (Chemical Engineering Journal, 2026)

Highly amphiphilicity-tailorable pineapple-like janus nanozymes with superior kinematic locomotion facilitates biphasic chemiluminescence analysis - Xin Jiang; Wan Wei; Yueming Zhao; Lingli Zhang; Wenwen Wang; Yuting Zhao; Zhongjie Zhu; Zhifeng Fu; Chengzhou Zhu; Hui Ouyang (Analytica Chimica Acta, 2026)

Waste eggshell-modified biochar for phosphorus recovery and its potential reuse as a sustainable fertilizer - Yixuan Feng; Yueming Chen; Xilin Guan; Zichao Zhao; Xinhao Gao; Xiaoning Liu; Shenzhong Tian (Journal of Environmental Chemical Engineering, 2026)

Sense, think, and robot control: Multimodal material recognition sensing integrated with large language model reasoning - Zuowei Wang; Fuzheng Zhang; Qijing Lin; Yueming Gao; Bin Sun; Hongze Ke; Na Liu; Bian Tian; Libo Zhao; Zhuangde Jiang (Chemical Engineering Journal, 2026)

Global assimilation of NRL MODIS aerosol optical thickness and its impact on aerosol direct radiative effect over a full year - Min Zhao; Tie Dai; Yueming Cheng; Daisuke Goto; Keiya Yumimoto; Guangyu Shi (Atmospheric Research, 2026)

Single-cell dissection of pleural and systemic immunity uncovers pathogen-specific immune reprogramming in tuberculosis versus lung adenocarcinoma - Sifei Yu; Yueming Liang; Jing Chen; Beiying Zhang; Chuling Zhang; Yuwen Zhao; Rong Yan; Yichu Nie; Xiaofan Mao (Inflammation Research, 2026)

Physicochemical properties of edible oxidized gum arabic–polylysine crosslinked films and their effects on the postharvest preservation of litchi - Dan Li; Huirong Cheng; Ling Xie; Hong Luo; Dandan Zhang; Jupeng Zhao; Yueming Jiang; Liang Gong (Postharvest Biology and Technology, 2026)

Quantifying the spatiotemporal characteristics and driving mechanisms of greenhouse gas emissions from the wastewater treatment sectors in Chinese cities - Xiaona Wang; Yueming Gao; Nana Zhao (Environmental Research, 2026)

Drivers of soil carbon and nitrogen cycling during plantation succession: linking aboveground plant communities with belowground microbial networks - Xianghua Zuo; Wei Zhao; Jinying Li; Yunxiao He; Yueming Zhao; Ming Xing; Jiangnan Li; Xia Chen (Plant and Soil, 2026)

Corrigendum to “Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach” [J Hazard Mater 501 (2026) 14065] - Kashif Ali Memon; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach - Memon Kashif Ali; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Mitigating methane emissions from municipal solid waste in Chinese cities - Yueming Gao; Yang Duan; Wei Zhang; Nana Zhao; Yuan Wang; Zhenyu Ding; Wenjun Wu; Dong Cao; Hongqiang Jiang (Journal of Environmental Management, 2026)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Pore structure modulation and surface functionalization boosted adsorption of PFAS on porous carbon: Experimental and theoretical investigations - Bei Zhang; Daiki Moriyama; Thilini Maheshika Herath; Huan Zhao; Yuqiao Bai; Yueming Dang; Wei Liu; Hiromichi Kato; Koichi Yamamoto; Yasuhide Mochizuki; Naoki Arimitsu; Akira Nakajima; et al. (Journal of Hazardous Materials, 2025)

Bioinspired graphene-based aerogel polyurethane multifunctional coatings with high-temperature resistance, anti-corrosion and anti-fouling properties - Yuping Liu; Limei Tian; Jie Zhao; Jiarun Tian; Yueming Wang; Jiyu Sun (Chemical Engineering Journal, 2025)

Enhancing the output of cellulose-based triboelectric nanogenerators via dual interfacial polarization effects - Feijie Wang; Suyang Wang; Hao Wang; Yichi Liu; Shiqiang Ouyang; Shenzhuo Zhang; Yueming Hu; Junhua Zhao; Shufeng Ma; Zhen Wu; Liqiang Wang (Carbohydrate Polymers, 2025)

Water Body Characterization and Classification in Coal Mining Subsidence Areas: Insights from the Huainan Coalfield - Yueming Sun; Yanling Zhao; Zhibin Li; Yanjie Tang (Natural Resources Research, 2025)

Phase congruency image mosaicking approach for aerial mid-wave infrared low-overlap array scanning images - Jiani He; Yueming Wang; Lixia Deng; Yitao Li; Zhao-Liang Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

MEK1 inhibition ameliorates mitochondrial-dependent apoptosis induced by deltamethrin in mouse hippocampal neuron HT22 cells - Lexing Wei; Yang Chen; Minjia Wu; Peixuan Ma; Huan Wang; Yueming Jiang; Michael Aschner; Jing Zhou; Guodong Lu; Lina Zhao; Xiaowei Huang (Toxicology in Vitro, 2025)

Synergistic impact of plant essential oil based microemulsion on lychee preservation in comparison to Prochloraz - Yujie Shen; Xin Zhou; Jupeng Zhao; Zhe Wang; Dandan Zhang; Lingrong Wen; Yueming Jiang; Liang Gong (Sustainable Chemistry and Pharmacy, 2025)

MAPK signaling mediated intestinal inflammation induced by endoplasmic reticulum stress and NOD2 - Siyuan Peng; Yan Zhao; Wang Jiang; Yan Long; Tian Hu; Mengling Li; Jinyue Hu; Yueming Shen (Molecular and Cellular Biochemistry, 2025)

Mitigating particulate matter dispersion from urban earthen sites: A case study of city walls in Zhengzhou, China - Yueming Wen; Yu Miao; Renjing Zhao; Yaowen Shi; Jiangxing Miao; Chang Lv; Guang Zhang (Sustainable Cities and Society, 2025)

Molecular characterization of large yellow croaker (Larimichthys crocea) coagulation factor Ⅶ-like and its function on macrophage proliferation and polarization - Yueming Chen; Han Zhao; Shuangshuang Cao; Hongjun Xie; Jieyu Huang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Freezing or searing: Unraveling the impact of extreme temperatures on poverty in China - Huiming Zhang; Shuyuan Wang; Kai Wu; Yueming (Lucy) Qiu; Shouyang Wang; Yongfan Zhao (Environmental Impact Assessment Review, 2025)

Interaction of Ca2+ and Fe3+ in co-precipitation process induced by Virgibacillus dokdonensis and its application - Huaxiao Yan; Yuping Liu; Haojuan Zhang; Shengping Jin; Zuozhen Han; Jusun Woo; Maurice E. Tucker; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Yueming Zhao; et al. (Journal of Environmental Sciences, 2025)

High-performance flexible organic field-effect transistor based on highly ordered poly(3-hexylthiophene) nanowires - Liangkun Lu; Meng Si; Shaobo Jin; Zirui Zhao; Xuling Liu; Liguo Dai; Yueming Zhou; Hongjie Yang; Guoyong Ye (Chemical Engineering Journal, 2025)

Acid strength controlled reaction pathways of propylene conversion under olefin cracking conditions over ZSM-5 - Qin Zhao; Fang Li; Yiran Wang; Yueming Liu; Mingyuan He (Fuel, 2024)

Co-removal and recycling of Ba2+ and Ca2+ in hypersaline wastewater based on the microbially induced carbonate precipitation technique: Overlooked Ba2+ in extracellular and intracellular vaterite - Huaxiao Yan; Xiaofei Zhu; Zhiyong Liu; Shengping Jin; Jilai Liu; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Maurice E. Tucker; et al. (Journal of Hazardous Materials, 2024)

Flexural vibration suppression behavior of sleeved phononic crystal pipes in thermal environment - Qian Geng; Guangyi Zhao; Xiongwei Yang; Zhushan Shao; Yueming Li (Engineering Structures, 2024)

Effect of Ba2+ on the biomineralization of Ca2+ and Mg2+ ions induced by Bacillus licheniformis - Huaxiao Yan; Xiaofei Zhu; Zhenjiang Li; Zhiyong Liu; Shengping Jin; Xiaotong Zhou; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; et al. (World Journal of Microbiology and Biotechnology, 2024)

Nitrogen-doped biochar/MnO2 as an efficient PMS activator for synergistic BPA degradation via non-free radical pathways in the water - Hang Chen; Xiao Li; Weizhuo Li; Jing Feng; Ying Zhao; Hexin Zhang; Yueming Ren (Journal of Environmental Chemical Engineering, 2024)

Benzotrithiophene-based covalent organic frameworks as efficient catalysts for artificial photosynthesis of H2O2 in pure water - Mingjie Liu; Peipei He; Hantao Gong; Zhenghua Zhao; Yueming Li; Kai Zhou; Yuemin Lin; Jing Li; Zongbi Bao; Qiwei Yang; Yiwen Yang; Qilong Ren; et al. (Chemical Engineering Journal, 2024)

Mn2+ recycling in hypersaline wastewater: unnoticed intracellular biomineralization and pre-cultivation of immobilized bacteria - Huaxiao Yan; Shengping Jin; Xiaolei Sun; Zuozhen Han; Hongmei Wang; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Maurice E. Tucker; Lirong Wei; et al. (World Journal of Microbiology and Biotechnology, 2024)

CD137L Inhibition Ameliorates Hippocampal Neuroinflammation and Behavioral Deficits in a Mouse Model of Sepsis-Associated Encephalopathy - Fang Qiu; Yueming Liu; Yang Liu; Zhuyun Zhao; Lile Zhou; Pengfei Chen; Yunbo Du; Yanmei Wang; Huimin Sun; Changchun Zeng; Xiaokang Wang; Yuqiang Liu; et al. (NeuroMolecular Medicine, 2023)
Anxiety manifestations and cognitive dysfunction are common sequelae in patients with sepsis-associated encephalopathy (SAE). Microglia-mediated inflammatory signaling is involved in anxiety, depression, and cognitive dysfunction during acute infection with bacterial lipopolysaccharide (LPS). However, the molecular mechanisms underlying microglia activation and behavioral and cognitive deficits in sepsis have not been in fully elucidated. Based on previous research, we speculated that the CD137 receptor/ligand system modulates microglia function during sepsis to mediate classical neurological SAE symptoms. A murine model of SAE was established by injecting male C57BL/6 mice with LPS, and cultured mouse BV2 microglia were used for in vitro assays. RT-qPCR, immunofluorescence staining, flow cytometry, and ELISA were used to assess microglial activation and the expression of CD137L and inflammation-related cytokines in the mouse hippocampus and in cultured BV2 cells. In addition, behavioral tests were conducted in assess cognitive performance and behavioral distress. Immunofluorescence and RT-qPCR analyses showed that hippocampal expression of CD137L was upregulated in activated microglia following LPS treatment. Pre-treatment with the CD137L neutralizing antibody TKS-1 significantly reduced CD137L levels, attenuated the expression of M1 polarization markers in microglia, and inhibited the production of TNF-α, IL-1β, and IL-6 in both LPS-treated mice and BV2 cells. Conversely, stimulation of CD137L signaling by recombinant CD137-Fc fusion protein activated the synthesis and release of pro-inflammatory cytokines in cultures BV2 microglia. Importantly, open field, elevated plus maze, and Y-maze spontaneous alternation test results indicated that TKS-1 administration alleviated anxiety-like behavior and spatial memory decline in mice with LPS-induced SAE. These findings suggest that CD137L upregulation in activated microglia critically contributes to neuroinflammation, anxiety-like behavior, and cognitive dysfunction in the mouse model of LPS-induced sepsis. Therefore, therapeutic modulation of the CD137L/CD137 signaling pathway may represent an effective way to minimize brain damage and prevent cognitive and emotional deficits associated with SAE.

Increased aerosol scattering contributes to the recent monsoon rainfall decrease over the Gangetic Plain - Tong Ying; Jing Li; Zhongjing Jiang; Guanyu Liu; Zhenyu Zhang; Lu Zhang; Yueming Dong; Chuanfeng Zhao (Science Bulletin, 2023)

A viologen-based conductive hydrogel enables iontophoresis devices powered by Mg biobattery - Yan Zhou; Shan Jiang; Xuenan Ma; Yueming Mu; Jiaxin Zhao; Qin Liang; Xiaoteng Jia; Danming Chao (Chemical Engineering Journal, 2023)

Electron-transfer pathways insights into contaminants oxidized by Cu-OOSO3- intermediate: Effects of oxidation states of Cu and solution pH values - Lele Zhao; Jiaming Zhang; Zhiping Zhang; Yujun Zhu; Yuan Zong; Chengying Bai; Tong Wei; Yueming Ren; Jun Ma (Journal of Hazardous Materials, 2023)

Novel insights into Co synergy and electron-transfer pathways during the oxidation of contaminants by Cu-OOSO3- in CuCo2Ox/peroxymonosulfate system - Lele Zhao; Jiaming Zhang; Yuan Zong; Jun Ma; Chengying Bai; Hexin Zhang; Yueming Ren (Journal of Environmental Chemical Engineering, 2023)

Study on structure-activity relationship (SAR) of simplified mirogabalin derivatives as voltage-gated calcium channel α2δ ligands for the treatment of chronic neuropathic pain - Yuanwen Zhang; Yueming Zheng; Qingqing Wu; Fuyun Tian; Chuanjun Ma; Haiyan Xu; Li Zhan; Zhaobing Gao; Guilong Zhao; Huihui Ti (Medicinal Chemistry Research, 2023)

ZnS quantum dots implanted polyaniline-wrapped corn straw catalysts for efficient photocatalytic nitrate reduction without external addition of hole scavengers - Shuo Wang; Ying Zhao; Jing Feng; Tong Wei; Jun Ma; Yueming Ren; Chengying Bai (Chemical Engineering Journal, 2023)

RETRACTED ARTICLE: RINT1 is a new suppression target to reduce colon cancer cell growth, migration and invasion through regulating ZW10/NAG-1 expression - Jinheng Xu; Meng Zhao; Shunxian Huang; Qian Wu; Minghe Bai; Xueli Zhao; Jixian Wang; Yueming Hu; Junwei Feng; Zhiyong Zhang (Molecular and Cellular Biochemistry, 2022)

Sodium P-aminosalicylic Acid Attenuates Manganese-Induced Neuroinflammation in BV2 Microglia by Modulating NF-κB Pathway - Junyan Li; Yue Deng; Dongjie Peng; Lin Zhao; Yuanyuan Fang; Xiaojuan Zhu; Shaojun Li; Michael Aschner; Shiyan Ou; Yueming Jiang (Biological Trace Element Research, 2021)

Protective Effects of Sodium Para-aminosalicylic Acid on Manganese-Induced Damage in Rat Pancreas - Xiaojuan Zhu; Bingyan Xie; Dianyin Liang; Wenxia Qin; Lin Zhao; Yue Deng; Pingjing Wen; Fang Xu; Michael Aschner; Yueming Jiang; Shiyan Ou (Biological Trace Element Research, 2021)

Sodium P-aminosalicylic Acid Inhibits Manganese-Induced Neuroinflammation in BV2 Microglial Cells via NLRP3-CASP1 Inflammasome Pathway - Yuanyuan Fang; Dongjie Peng; Yuan Liang; Lili Lu; Junyan Li; Lin Zhao; Shiyan Ou; Shaojun Li; Michael Aschner; Yueming Jiang (Biological Trace Element Research, 2021)

Representativeness and Redundancy-Based Band Selection for Hyperspectral Image Classification` - Yufei Liu; Xiaorun Li; Yueming Feng; Liaoying Zhao; Wenqiang Zhang (International Journal of Remote Sensing, 2021)

Cholesterol 25-hydroxylase suppresses rabies virus infection by inhibiting viral entry - Yueming Yuan; Zongmei Wang; Bin Tian; Ming Zhou; Zhen F. Fu; Ling Zhao (Archives of Virology, 2019)

A global survey of bacterial type III secretion systems and their effectors - Yueming Hu; He Huang; Xi Cheng; Xingsheng Shu; Aaron P. White; John Stavrinides; Wolfgang Köster; Guoqiang Zhu; Zhendong Zhao; Yejun Wang (Environmental Microbiology, 2017)
Summary The type III secretion system (T3SS) is an important genetic determinant that mediates interactions between Gram‐negative bacteria and their eukaryotic hosts. Our understanding of the T3SS continues to expand, yet the availability of new bacterial genomes prompts questions about its diversity, distribution and evolution. Through a comprehensive survey of ∼20 000 bacterial genomes, we identified 174 non‐redundant T3SSs from 109 genera and 5 phyla. Many of the bacteria are environmental strains that have not been reported to interact with eukaryotic hosts, while several species groups carry multiple T3SSs. Four ultra‐conserved Microsynteny Blocks (MSBs) were defined within the T3SSs, facilitating comprehensive clustering of the T3SSs into 13 major categories, and establishing the largest diversity of T3SSs to date. We subsequently extended our search to identify type III effectors, resulting in 8740 candidate effectors. Lastly, an analysis of the key transcriptional regulators and circuits for the T3SS families revealed that low‐level T3SS regulators were more conserved than higher‐level regulators. This comprehensive analysis of the T3SSs and their protein effectors provides new insight into the diversity of systems used to facilitate host‐bacterial interactions.

Spatial variability of soil arsenic and its association with soil nitrogen in intensive farming systems - Yueming Hu; Zhenglei Jia; Jiachang Cheng; Zhizhong Zhao; Feixiang Chen (Journal of Soils and Sediments, 2016)

Molecular characterization of the celiac disease epitope domains in α-gliadin genes in Aegilops tauschii and hexaploid wheats (Triticum aestivum L.) - Zhenze Xie; Congyan Wang; Ke Wang; Shunli Wang; Xiaohui Li; Zhao Zhang; Wujun Ma; Yueming Yan (Theoretical and Applied Genetics, 2010)